Lgbtqi+: Level of Awareness and Inclusivity Among College Students (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The primary purpose of this study was to determine the level LGBTQI+: Level of Awareness and Inclusivity among BSED and BEED students of Altavas College. The researchers collected the data by using an electronic web-based questionnaire through the use of survey tool using questions modified from level of awareness and level of inclusivity. The survey comprised 2 subsections according to the participant's level of awareness and a question corresponding to each respondent's level of inclusivity. The analysis was perceived using the frequency count, percentage, and mean. Descriptive analyses were computed. The result showed that on the level of awareness, the respondents were "Very HiglyAware." This signifies that the respondents has a very high level of awareness towards LGBTQI+. The level of inclusivity among Altavas College students was described as "Vey High Inclusive". It indicates that the respondents are much willing to accept LGBTQI+ as a part of the society.